(untitled) (REMUNOM, 2025)
The mass-spring system is a classical model in Physics that represents oscillatory phenomena through the relationship between force and deformation, as described by Hooke’s Law. This work aims to experimentally investigate this system and mathematically model it, highlighting its various interdisciplinary applications. The research began with a theoretical review of the system’s functioning, followed by experiments and the formulation of a mathematical model based on differential equations. The analyses explore physical quantities such as the spring constant, gravitational acceleration, and elastic potential energy. Furthermore, the study demonstrates the applicability of the mass-spring system in fields such as civil engineering (analysis of structures subject to seismic vibrations), automotive mechanics (suspension systems), electrical engineering (RLC circuits), medicine (prosthetics and biomechanics), and quantum physics (harmonic oscillators). Thus, the work reinforces the pedagogical and scientific value of the topic, contributing to an integrated understanding of theory, practice, and real-world applications. Keywords: Mass-spring system; Hooke’s Law; Mathematical modeling; Interdisciplinary applications.